Ovarian clear cell carcinoma with uterine intramural recurrence: Case report of ovarian clear cell carcinoma with fertility sparing treatment - Ting Yu Chang; Chiung-Yi Yeh; Chih-Yi Yang; Wu-Chou Lin; Chien-Chu Huang; Yao-Ching Hung (Elsevier, 2024)
Objective: Ovarian clear cell carcinoma has a poor prognosis in comparison with other pathological types of epithelial ovarian carcinoma. It also has relative resistance to first-line platinum-based chemotherapy with a great risk of recurrence. Case report: We report a case of recurrent ovarian clear cell carcinoma status after left salpingo-oophorectomy (fertility-sparing debulking operation) and six courses of adjuvant chemotherapy (paclitaxel (175 mg/m2)/carboplatin (AUC 6)). However, two years after diagnosis, elevated CA-125 accompanied by an intrapelvic mass was noted. Uterine intramural recurrence was found during the second laparotomy. She was treated with right salpingo-oophorectomy and abdominal hysterectomy combined with systemic chemotherapy administration (paclitaxel (175 mg/m2)/carboplatin (AUC 6)) and maintenance therapy (bevacizumab (7.5 mg/kg)). There was no other recurrence until one and a half years postoperatively, and the patient was tumor free with regular follow-up. Conclusion: In young patients with stage I ovarian clear cell carcinoma, fertility-sparing surgery was considered. Most patients will suffer from tumor recurrence, and also intrauterine recurrence rarely happen.